Interprofessional team-based primary health care for adults with intellectual and developmental disabilities: a scoping review protocol. (December 2019) - Bobbette, Nicole; Donnelly, Catherine; Ufholz, Lee-Anne; Duggan, Jane; Weatherbed, Emily
ABSTRACT: Objective: This review aims to examine the state of the evidence for interprofessional team-based primary health care for adults with intellectual and developmental disabilities. Introduction: Adults with intellectual and developmental disabilities have complex health needs, as well as experience health service inequities. Interprofessional primary healthcare teams offer access to comprehensive primary health care and are recommended as an approach to improve the health of this population. At present, limited information is available regarding what services interprofessional primary healthcare teams provide and how services are evaluated specific to the care of adults with intellectual and developmental disabilities. Inclusion criteria: This review will consider all studies that reference individuals with intellectual and developmental disabilities who are 18 years and over. It will consider all studies that refer to interprofessional healthcare provision within a primary healthcare team context. Interprofessional care is the term that will be used to describe services provided by interprofessional health providers (e.g. nurses, dietitians, social workers) in these teams. Work completed by physicians and nurses within traditional general practices will be excluded. Methods: This review will be conducted according to the JBI methodology for scoping reviews. It will consider quantitative, qualitative and mixed methods study designs for inclusion. In addition, systematic reviews, program descriptions, clinical reviews and opinion papers will be considered. The review will consider all studies published since 2000 in English or French. All duplicates will be removed from identified citations. A data extraction tool will assist reviewers to identify and synthesize findings from selected papers.